Self-extinguishment of cross-laminated timber. (April 2019) - Crielaard, Roy; van de Kuilen, Jan-Willem; Terwel, Karel; Ravenshorst, Geert; Steenbakkers, Pascal
Abstract: Cross-laminated timber, or CLT, is receiving attention for its potential application in tall building structures. As a combustible material, one of the main challenges for the construction of these buildings is the fire risk that results from its use in the structure. Unprotected CLT can burn along with the fuel load present in a compartment. Irrespective of the structure's fire resistance rating, it is uncertain whether the structure will be totally consumed in the event of a complete burnout. If the structure would continue to burn, this could result in collapse of the building. Alternatively, the fire could decay by self-extinguishment. Self-extinguishment of CLT was investigated with a theoretical model that describes the conditions under which it could be achieved. Two series of experiments were conducted to quantify these conditions. It was concluded that there is a potential for self-extinguishment of CLT if fall-off of charred layers is prevented by applying sufficiently thick lamellae, if the heat flux on the CLT during smouldering is below 5–6 kW/m 2, and if the airflow over the surface during smouldering is limited to a speed of 0.5 m/s. An exploration towards design implementation is presented. Graphical abstract: Image 100 Highlights: There is a potential for CLT to self-extinguish. Prevent char fall-off with sufficiently thick lamellae. Limit heat flux during smouldering to ≤5–6 kW/m 2 Ensure sufficiently low airflow with speed ≤0.5 m/s at these levels of heat flux.